PENDAPATAN DAN HARGA POKOK PRODUKSI PENGOLAHAN JAHE DAN KENCUR MENJADI JAMU SEHAT INSTAN - Saputra, Muhammad Ilham; Zulkarnain, Zulkarnain; Yatmin, Yatmin; Rakhmiati, Rakhmiati; Isnaini, Soni; Maryati, Maryati; Krisnarini, Krisnarini (AGROTEKSOS, 2025)
Biopharmaceutical plants are plants that can be utilized for medicinal properties and used to prevent disease. The aim of the research is to analyze the income and production costs of processing ginger and galangal into instant herbal medicine powder in the Women Farmers Group of Terbanggi Besar Village, Terbanggi Besar District, Central Lampung Regency. The research method uses quantitative descriptive methods with sample determination using Purposive Sampling techniques with the consideration that Kampunga Terbanggi Besar, Terbanggi Besar District, Central Lampung Regency is a village that is a center for producing ginger and kencur. The research results show that the income earned by the Karya Agung Women's Farmers Group from processing ginger into instant herbal powder is IDR. 123,330/month and the income from processing kencur into instant herbal powder is IDR. 129,161/month. It is known that the r/c ratio is 1.22, which means this business is profitable and worth pursuing. Then the results of calculating the cost of production using the full costing method for the Karya Agung Women's Farmers Group for processing ginger into instant herbal medicine powder is IDR. 20,595/packaging and for processing galangal into instant herbal medicine powder, namely Rp. 20,387/packaging.